Analisis Kepuasan Pelanggan dan Kepatuhan Prinsip Syariah terhadap Loyalitas Tamu di Hotel Harris - Khizqil Panca Subagja; Imas Kania Rahman; Salati Asmahasamah (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to examine the effect of customer satisfaction and compliance with sharia principles on guest loyalty at a Muslim-friendly hotel. The research employs a quantitative approach using a survey method involving 100 Muslim guests who had stayed at Harris Hotel. Data were collected through a structured questionnaire using a Likert scale and analyzed using multiple linear regression with SPSS. The results indicate that customer satisfaction has a positive and significant effect on guest loyalty. In addition, compliance with sharia principles also positively and significantly influences guest loyalty. Simultaneously, both variables significantly affect guest loyalty. These findings suggest that the integration of service quality and adherence to sharia principles is an important strategy for modern hotels in enhancing Muslim guest loyalty.